(untitled) (Il Risorgimento. Rivista di storia moderna e contemporanea, 2024)
The history of the Ottaviani of Parghelia in Calabria, merchants in the 18th century between Messina, Marseille and the South of Italy and in the 19th century the first tanning industrialists in Sicily, demonstrates the contribution of a small village to international trade. The moral dimension of the family economy is highlighted in the transition from the 18th to the 19th century, from the revolutionary era to the unification of Italy. The Ottaviani embody the passage from an eighteenth-century identity, based in the local and cosmopolitan dimensions of the mercantile world, to the nineteenth-century concept of nation, in which the municipalist sentiment nevertheless appears to characterize from South the unitary process.